Essential mapwork skills - Ross, Simon R. J. (Oxford University Press, 2014)
A unique collection of case study-based activities, using a variety of thematic, topographical and topological maps, as well as accompanying aerial, ground and satellite photographs to develop students' photographic and map interpretation skills in context.